The Effect of the Application of Flexible Working Hours on Work Stress in Account Representative of KPP Pratama Cilacap - Nugroho, Wahyu Aji; Kusumo, Rudy Mikiyanto (Lentera Ilmu Nusantara, 2024)
In carrying out its duties and functions, the KPP Pratama Cilacap Account Representative is prone to experiencing job stress. This research aims to find out whether the application of flexible working hours affects the job stress experienced by KPP Pratama Cilacap Account Representatives. This study uses two variables, namely flexible working hours as the independent variable and job stress as the dependent variable. In this study, the hypothesis proposed is that the application of flexible working hours has an effect on job stress at KPP Pratama Cilacap Account Representatives. Data collection was carried out by distributing closed questionnaires directly to the respondents and conduct interviews with respondents randomly. The population of this study were all KPP Pratama Cilacap Account Representatives, totaling 31 people. Questionnaire data processing was carried out using IBM SPSS Statistics 25 software with a simple linear regression analysis method. The analysis of this study shows that the job stress of the KPP Pratama Cilacap Account Representative is not affected by the application of flexible working hours.